New data on parasitoids living in oak (Quercus spp.) galls from Georgia (Sakartvelo) - Nozadze, Marine; Japoshvili, George (The Journal of Nature Studies - Annals of Agrarian Science, 2025)
Eighteen species of Chalcid inquiline wasps have been reared during our survey from Oak galls from all regions of Georgia. Four genera and 10 species were new records for the Caucasus, with two more new records for Georgia, and one species with a new host record was also confirmed. Recorded chalcids belong to 7 families and 12 genera.